Analisis Perbandingan Sistem Investigasi Kematian Pediatri di Berbagai Negara - Liauw, Djai Yen; Tantra, Deven Aleron; Koesuma, Freddie Wijaya; Grace; Budiono, Jolene; Putri, Lidwina Nadia Adinda; Wijaya, Stephanie Jeanne; Sharon, Sonya Hedva; Valerie; Silitonga, Virnalisi Lestari Romauli; Palarogo, Yosua Dima Agung (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Introduction: Sudden infant death is a medical and legal issue that requires investigation involving relevant institutions. In various countries, differences in standards, resources, and systems pose challenges. Purpose: To examine the systems and methods of investigating sudden child deaths for the prevention of pediatric mortality. Methods: Databases searched included Google Search, PubMed, and Google Scholar for studies published up to 2024. The analysis applied keywords such as ‘pediatrics,’ ‘death,’ ‘investigation,’ ‘guidelines,’ and ‘system. Results: In Indonesia, the pediatric death investigation system is handled by the Ministry of Health and the Indonesian Police; however, there are limitations, including a shortage of forensic personnel and inadequate autopsy facilities. In contrast, developed countries have stricter regulations and better documentation systems. Several institutions have worked to establish international standards for child death investigations through the Inter-agency Guidelines on Child Death Review. These guidelines are essential to standardize the investigation system and create systematic reporting to prevent pediatric deaths. Conclusion: Despite standardization efforts, investigation systems remain varied between countries, depending on conditions and resources. To improve the system in Indonesia, enhanced forensic personnel and a digitalized reporting system are needed.m